In the Company of the Poor: Conversations with Dr. Paul Farmer and Fr. Gustavo Gutiérrez, edited by Michael Griffin and Jennie Weiss Block, Orbis Books, Maryknoll, NY, 2013. - W Meredith Long (Health for All Nations, 2014)
Dr. Farmer is essentially an activist-a doer-who remains uncomfortable with the foundational truths of Christian experience, grace, conversion, suffering, and a living faith. At least in this book, Dr. Farmer sips selectively from the spring that has clearly given life to Fr. Gutiérrez for over 80 years. Dr. Farmer uncharacteristically gave no response to Fr. Gutiérrez's final chapter, "The Option for the Poor Arises from Faith in Christ". Fr. Gutiérrez's chapters reflect his response to the poor in light of biblical teaching: Dr. Farmer's chapters reflect his response to poverty, more specifically related to health, in the light of Fr. Gutiérrez's teachings. Together, however, the passionate, pragmatic activist and the passionate, reflective theologian challenge those of us involved in health to a biblical and holistic understanding and response to the suffering and early death of the poor.